Managing the built heritage of the vineyars of Ica: Rural tourism and community museums - Iju Ireijo, Natalia (2018)
Our research proposes a local development alternative that combines two touristic plans. The first one is focused on participative community museums, as the ones in Pisac, Cuzco and Leymebamba, Amazonas, among some others. There are not many yet, although this international museological trend has been present since the 70s. The second one focuses on rural tourism, looking for the active involvement of the local population through activities related to their daily environment. Within this context, we propose the creation of participative community museums that manage the built heritage of Ica’s vineyards, along with the promotion of rural tourism. This approach intends to promote local development and sustainability.